1976
DOI: 10.1128/aac.10.4.592
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Activity of Netilmicin, Gentamicin, Amikacin, and Tobramycin Against Pseudomonas aeruginosa and Enterobacteriaceae

Abstract: Netilmicin (Sch 20569), a semisynthetic aminoglycoside antibiotic, was compared with gentamicin, tobramycin, and amikacin against 242 clinical isolates of Pseudomonas and Enterobacteriaceae . The minimum inhibitory concentration (MIC) was determined in both solid and liquid media. Netilmicin exhibited typical aminoglycoside properties, such as little effect of inoculum size on MIC, relatively small gap between MIC and minimum bactericidal concentration, and poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 7 publications
3
17
0
Order By: Relevance
“…There were 18 females and 9 males. The underlying diseases were: hemoproliferative malignancy, 2; cirrhosis and hepatitis, 7; paraplegia, 3; renal transplantation, 3; chronic renal failure, 1; uretero-ileal conduit after resection of bladder carcinoma, 3; diabetes mellitus, 1; and sickle thalassemia, 1 Table I (b) RS. Shock and enterobacter bacteremia, without an identifiable portal of entry, occurred in a 52-year-old female in the hospital because of a myocardial infarction.…”
Section: Materiais and Methods Thirty-one Patients On The Medical Andmentioning
confidence: 99%
“…There were 18 females and 9 males. The underlying diseases were: hemoproliferative malignancy, 2; cirrhosis and hepatitis, 7; paraplegia, 3; renal transplantation, 3; chronic renal failure, 1; uretero-ileal conduit after resection of bladder carcinoma, 3; diabetes mellitus, 1; and sickle thalassemia, 1 Table I (b) RS. Shock and enterobacter bacteremia, without an identifiable portal of entry, occurred in a 52-year-old female in the hospital because of a myocardial infarction.…”
Section: Materiais and Methods Thirty-one Patients On The Medical Andmentioning
confidence: 99%
“…This study was undertaken as a result of our interest in determining whether there were any important differences between the aminoglycoside antibiotics gentamicin and tobramycin. A review of the literature indicated only minor differences in in vitro antibacterial activity (1,6,8,14,20,31). Gentamicin is slightly more active against Serratia species, and tobramycin is slightly more active against isolates of Pseudomonas aeruginosa.…”
mentioning
confidence: 99%
“…(6) Salmonella spp. (5) Vibrio parahaemolyticus (3) Gaffkya tetragena (1) Sarcina lutea (1) Edwardsiella tarda (1) Herellea vaginicola (1) Klebsiella oxytoca (1) Providencia spp. (2) Shigella dysenteriae (1 to assess the nephrotoxicity of the two compounds were urine volume, protein excretion, osmolality, microscopic characteristics, blood chemistry, and histopathology.…”
Section: Resultsmentioning
confidence: 99%